1995
DOI: 10.1161/01.str.26.4.620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thalamic Hematoma on Six-Month Mortality and Motor and Cognitive Functional Outcome

Abstract: The extension and volume of hematomas, indicating direct cerebral damage, are useful indicators of mortality from thalamic hemorrhage, motor functional outcome, and level of activities of daily living after 6 months. The disturbance of consciousness and ventricular extension of the hematoma, suggesting diffuse brain damage, could be predictors of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…Several studies have demonstrated that patients with acute thalamic hemorrhage, particularly with extension to the ventricles, often require surgical intervention and have a poor prognosis. [23][24][25] Although the present data cannot specify the mechanism by which combined damage to the Pt and Th (the PϩT group) leads to enhanced functional outcome, there are a number of candidate regions crucial for reorganization that were not damaged. In the study patients, the areas that were commonly intact include the PMC, SMA, caudate, globus pallidus, the nucleus ventralis anterior of the Th, and the anterior limb of the internal capsule.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have demonstrated that patients with acute thalamic hemorrhage, particularly with extension to the ventricles, often require surgical intervention and have a poor prognosis. [23][24][25] Although the present data cannot specify the mechanism by which combined damage to the Pt and Th (the PϩT group) leads to enhanced functional outcome, there are a number of candidate regions crucial for reorganization that were not damaged. In the study patients, the areas that were commonly intact include the PMC, SMA, caudate, globus pallidus, the nucleus ventralis anterior of the Th, and the anterior limb of the internal capsule.…”
Section: Discussionmentioning
confidence: 84%
“…The remaining 78 references [24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100]described 68 different studies and 83 separate prognostic models. We classified the models on the basis of whether they were community or hospital-based, the pathological type of stroke included, and the type and timing of the outcome (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thalamic hemorrhage is a severe clinical condition with in-hospital mortality rate of 19%, and symptom-free at discharge from the hospital documented in only 2.1% [15]. The mortality rate of thalamic hemorrhage ranges between 17% and 52% in the experience of different authors [14,16]. On the other hand, the mortality rate of thalamic hemorrhage is generally lower than that of brainstem hemorrhages or cerebral hemorrhages of multiple topographies, which show a very high in-hospital mortality rate usually greater than 40% [5].…”
Section: Thalamic Hemorrhagementioning
confidence: 99%